Perfect phrases for healthcare professionals : hundreds of ready-to-use phrases - Rotte, Masashi (Perfect phrases series., 2012)
In the fast-paced environment of healthcare, tense, complicated, and unpredictable interactions are a guarantee. Clear communication is an absolute necessity for resolving workplace conflicts and keeping patients fully educated in what can literally be life or death situations.